THE EFFECTIVE WAYS OF TEACHING ENGLISH THROUGH CLUSTER SYSTEM (British Journal of Global Ecology and Sustainable Development, 2023)
The article is about some ways for developing writing skills so that they can apply them in their academic life. Data was collected using a questionnaire which was formulated on the basis of different processes of writing and classroom practice by the learners. The survey was conducted among the students who were studying or had taken language skills courses at the Department of English in a private university of Uzbekistan. Based on the findings, some practical recommendations have been made for all three stakeholders: learners, teachers, and institutions.